Study on a robot 3D laser radar information collection system - Chen, W.; Shen, J.; Xue, J. (Journal of Digital Information Management, 2013)
This paper studies a low-cost computerbased 3D laser radar collection system. First, the control of actuator is realized by serial communication and the 2D image is captured from lines to surface, then denoise processing calibration is carried out by using Open CV. By using Irrlicht3D engine, the point cloud data is to be rendered to convert the 2D images to the 3D effect. Robot's collection on external image is achieved through the study of Open CV learning that combined with VC2008.
Keywords: 3D laser radar; Information collection; Low-cost